2009
DOI: 10.1007/s00296-009-0854-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibody against mutated citrullinated vimentin: a new sensitive marker in the diagnosis of rheumatoid arthritis

Abstract: The aim of this study was to determine the performance of antibodies against mutated citrullinated vimentin (anti-MCV) in comparison with antibodies to cyclic citrullinated peptides (anti-CCP) in patients with rheumatoid arthritis (RA). Serum levels of anti-MCV and anti-CCP were determined in 193 patients with RA and 332 controls, and sensitivity and specificity were calculated. In a separate analysis of 86 patients, the anti-MCV levels were compared to disease activity. Sensitivity of anti-MCV versus anti-CCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 11 publications
6
40
2
Order By: Relevance
“…[6,7,10,11,14,16] The results of the present study also support this outcome for the anti-MCV-548 kit. However, regarding the anti-MCV-248 kit, there was no statistically significant difference in sensitivity and specificity between anti-CCP-2 and anti-MCV antibodies.…”
Section: Assaysupporting
confidence: 77%
See 3 more Smart Citations
“…[6,7,10,11,14,16] The results of the present study also support this outcome for the anti-MCV-548 kit. However, regarding the anti-MCV-248 kit, there was no statistically significant difference in sensitivity and specificity between anti-CCP-2 and anti-MCV antibodies.…”
Section: Assaysupporting
confidence: 77%
“…[7,10] Wagner et al [7] found anti-MCV positivity to be 13.6% (n=8) in anti-CCP negative patients (59 patients). In a study by Nicaise-Roland et al, [10] anti-MCV was found to be positive in 18.4% (n=14) of anti-CCP negative patients (n=76).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Keskin et al [21] found that the measurement of serum anti-MCV levels is useful for diagnosis of RA and combined use of anti-MCV and RF antibodies may be more useful prognostic factor than RF and anti-CCP. The discrepancy between various studies can be explained by the difference in: (i) patient populations [22], (ii) early RA [23,24] or established RA [12,25], or (iii) number of cases studied [15].…”
Section: Discussionmentioning
confidence: 99%